Perancangan Daycare “ Aisyah Ralin ” Dalam Membangun Lingkungan Belajar Sejak Dini Yang Islami Dan Menyenangkan Di Mojotengah Dusun Condong - Ahmad Adhib; Ahmad Robihan; Firda Fajria Nur Azilla; Sinta Nadiatun Khalifah; Fina Sofiatun Nabila; Muhammad Hasyim Abdurrohman; Naela Hasna; Devina Kumaladewi; Lutfiah Karimah; Mentari Dewi Fortuna; Nanda Sara Asifa; Rahmat Hidayatullah; Ahmad Khamami; Dimas Setiawan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
The Community Service Lecture (KPM) at Universitas Sains Al-Qur'an, Central Java, in Wonosobo focuses on student development and community empowerment. Group 22 Mojotengah 2025 initiated a research-based program titled "Designing 'Aisyah Ralin' Daycare to Build an Islamic and Enjoyable Early Childhood Learning Environment in Mojotengah, Condong Hamlet." Using the Research and Development (R&D) method, the program aims to educate and train children from an early age while supporting working parents by providing a safe and nurturing childcare environment. This initiative also creates job opportunities for mothers in Mojotengah Village, contributing to community welfare. Daycare centers (TPA) play a vital role in child development by offering a space for play and learning. A well-designed, child-friendly environment ensures safety and comfort for children. The project consists of several stages: preparation (field observation), planning (space design for activities), and implementation (arranging furniture to enhance safety and efficiency). The expected outcomes include a safe and supportive daycare environment and new employment opportunities for local women, ultimately improving the quality of early childhood education and overall community welfare in Mojotengah.